Marital Status and Overall Survival in Patients with Resectable Pancreatic Cancer: Results of an Ancillary Analysis of NRG Oncology/RTOG 9704. (16th December 2019) - Reyngold, Marsha; Winter, Kathryn A.; Regine, William F.; Abrams, Ross A.; Safran, Howard; Hoffman, John P.; Mowat, Rex B.; Hayes, John P.; Kessel, Ivan L.; DiPetrillo, Thomas; Narayan, Samir; Chen, Yuhchyau; et al.
Abstract: Background: Several registry‐based analyses suggested a survival advantage for married versus single patients with pancreatic cancer. The mechanisms underlying the association of marital status and survival are likely multiple and complex and, therefore, may be obscured in analyses generated from large population‐based databases. The goal of this research was to characterize this potential association of marital status with outcomes in patients with resected pancreatic cancer who underwent combined modality adjuvant therapy on a prospective clinical trial. Materials and Methods: This is an ancillary analysis of 367 patients with known marital status treated on NRG Oncology/RTOG 97‐04. Survival analysis was performed using the Kaplan‐Meier method and compared using the log‐rank test. Multivariate analysis was performed using the Cox proportional hazards regression model. Results: Of 367 patients, 271 (74%) were married or partnered and 96 (26%) were single. Married or partnered patients were more likely to be male. There was no association between marital status and overall survival (OS) or disease‐free survival (DFS) on univariate (hazard ratio [HR], 1.09 and 1.01, respectively) or multivariate analyses (HR, 1.05 and 0.98, respectively). Married or partnered male patients did not have improved survival compared with female or single patients. Conclusion: Ancillary analysis of data from NRG Oncology/RTOG 97‐04 demonstrated no association between marital and/or partner status and OS or DFS in patients with resected pancreatic cancer who received adjuvant postoperative chemotherapy followed by concurrent external beam radiation therapy and chemotherapy. Clinical trial identification number . NCT00003216. Abstract : Evidence suggests a survival advantage for married compared with single patients with pancreatic cancer. This article examines the effect of marital status on survival for this cohort of patients with resected pancreatic cancer, based on data from NRG Oncology/RTOG 97‐04.